Synthesis and Characterization of Graphene-Based Nanosheets via Chemical Reduction of Expanded Graphite Oxide - Zhang, Feng-Jun; Jang, Won-Kweon; Oh, Won-Chun (Asian Journal of Chemistry, 2011)
Reduced graphene-based sheets were produced by reduction of a colloidal suspension of expanded graphite oxide sheets in water with hydrazine hydrate. These sheets were comprehensively characterized by Fourier transform infrared spectroscopy, energy dispersive X-ray analysis, X-ray diffraction, scanning electron microscopy, transmission electron microscopy and Raman spectroscopy. X-ray diffraction, energy dispersive X-ray and Fourier transform infrared measurements indicate the formation of strong functional groups of expanded graphite oxide. From the transmission electron microscopy images, graphene based nanosheets could be found in the reduction of expanded graphite oxide. The Raman spectra indicated that the stacking structure and agglomerated morphology of graphene based nanosheets is deduced.